2016
DOI: 10.1007/s10792-016-0187-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of eyelid sebaceous gland carcinoma based on the tumor (T) category of the American Joint Committee on Cancer (AJCC) classification

Abstract: The purpose of this study was to evaluate the clinical features and prognosis of eyelid sebaceous gland carcinoma (SGC) based on the T category of the American Joint Committee on Cancer (AJCC) classification (7th edition). This is a retrospective interventional case series study. Based on the T category of the AJCC classification, 191 patients with eyelid sebaceous gland carcinoma were classified as T1 (n = 1, 1 %), T2 (n = 111, 58 %), T3 (n = 76, 40 %), and T4 (n = 3, 2 %). Based on multivariate analysis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 22 publications
4
38
0
2
Order By: Relevance
“…Similarly, in the Korean cohort, T2b or worse were associated with lymph node metastasis 10. The Indian cohort also found that the risk of systemic metastasis and death was related to an increasing T category 9. However, in the Japanese cohort, the authors found that tumours even smaller than T2a were associated with tumour metastasis 8.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in the Korean cohort, T2b or worse were associated with lymph node metastasis 10. The Indian cohort also found that the risk of systemic metastasis and death was related to an increasing T category 9. However, in the Japanese cohort, the authors found that tumours even smaller than T2a were associated with tumour metastasis 8.…”
Section: Discussionmentioning
confidence: 95%
“…Staging of an eyelid tumor is based on the TNM classification and is a critical element in determining the appropriate treatment, a key factor defining prognosis, and will assist in the evaluation of the results of the treatment [8,9,21,22]. Regarding eyelid tumors, different T-stagings are applied depending on the type of tumor and on the layer of origin of the tumor within the eyelid.…”
Section: Discussionmentioning
confidence: 99%
“…A higher risk for recurrence or metastasis has been reported in patients with symptoms over 6 months, involvement of both upper and lower eyelids, multicentric origin, diffuse or a non-lobular pattern, pagetoid spread, orbital involvement, perineural invasion and stage T2b (AJCC 7th -edition) or worse [60,61]. In a chinese study of 238 patients, risk factors for tumor-related death were orbital involvement, the greatest tumor basal diameter, pagetoid spread and lymph node metastasis at initial diagnosis [62].…”
Section: Follow-upmentioning
confidence: 99%
“…Stage T2b (AJCC 7th-edition) and stage T2c (AJCC 8-th edition) or a more advanced disease is reported to correlate with regional lymph node metastasis and T2b or T3a or worse (AJCC 7th-edition) and stage T2c (AJCC 8-th edition) are reported to correlate with distant metastases [11,15,46,58]. Kaliki et al [61] estimate of lymph node metastasis at 5 and 10 years are 0 and 0% for T1, 11and 11% for T2, 44 and 59% for T3 and 100 and 100% for T4, [13]…”
Section: Follow-upmentioning
confidence: 99%